2022
DOI: 10.3390/d14070548
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Characterization of Endangered Indian Mithun (Bos frontalis), Indian Bison/Wild Gaur (Bos gaurus) and Tho-tho Cattle (Bos indicus) Populations Using SSR Markers Reveals Their Diversity and Unique Phylogenetic Status

Abstract: Mithun (Bos frontalis) or gayal and Indian Bison or wild gaur (Bos gaurus) are listed among the rare and endangered bovine species of India. The remote location of mithun in four North Eastern Hill states (Arunachal Pradesh, Nagaland, Manipur, and Mizoram), scattered population size, and non-availability of genetic diversity status are major limitations towards devising a suitable breeding and conservation policy of these species. Since several studies have demonstrated the successful applicability of microsat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 57 publications
1
4
1
Order By: Relevance
“…The number of ROHs observed in LSS was significantly higher than in many other sheep populations [64,65], potentially attributable to the detection of millions of SNPs. Among different ROHs, the ROH 0.1-0.2 Mb proportion was the highest, and the distribution of ROH lengths in the LSS genome closely followed an L-shaped distribution, consistent with results in sheep [66], goats [40,53], cattle [67], and pigs [68]. Detailed analyses indicate that the ROH patterns in LSS genomes primarily stem from historical inbreeding among individuals.…”
Section: Discussionsupporting
confidence: 74%
“…The number of ROHs observed in LSS was significantly higher than in many other sheep populations [64,65], potentially attributable to the detection of millions of SNPs. Among different ROHs, the ROH 0.1-0.2 Mb proportion was the highest, and the distribution of ROH lengths in the LSS genome closely followed an L-shaped distribution, consistent with results in sheep [66], goats [40,53], cattle [67], and pigs [68]. Detailed analyses indicate that the ROH patterns in LSS genomes primarily stem from historical inbreeding among individuals.…”
Section: Discussionsupporting
confidence: 74%
“…The average expected and observed heterozygosity of gaur in KPM was lower than in Vietnam, while the observed heterozygosity of some loci was higher. The number of alleles was lower than in the studies in India, both samples from wild populations (Farah et al 2021) and from zoos (Mukherjee et al 2022). On average, the heterozygosity of gaur in this study was lower than in India.…”
Section: Genetic Analysiscontrasting
confidence: 79%
“…In general, genetic diversity is compared over time or among populations. Since there was no microsatellite-based genetic diversity report of other gaur populations in Thailand, the results of our study were compared with the gaur population in Vietnam (Nguyen et al 2007) and India (Farah et al 2021;Mukherjee et al 2022). Microsatellite loci used for genetic diversity study in India varied, some loci were different from our study.…”
Section: Genetic Analysismentioning
confidence: 65%
“…The microsatellite alleles were divided into 10 frequency classes, allowing us to determine whether the distribution shows the normal L-shaped form with an abundance of low-frequency alleles (0.01 to 0.1) (Luikart et al,1998). Such genetic bottlenecks are mostly associated with zoos, forest conditions, or relatively small and limited population size in isolated areas (Zhang et al, 2002;Luenser et al, 2005;Mukherjee et al, 2022). Although officially registered in Artvin and Ardahan provinces 138 362 hives (Gül & Nergiz, 2022); looking at the variation source in the Caucasian bee population, it was found that variation is insufficient and the variations come from among individuals, not among the populations.…”
Section: Resultsmentioning
confidence: 99%
“…Many molecular markers such as restriction fragment length polymorphism (RFLP), random amplified polymorphic DNA (RAPD) and mitochondrial DNA (mtDNA) analyses have been used in honey bee population genetics studies, but for the last 20 years, microsatellite loci have been quite widely used due to their features such as high polymorphism, multiallelicity, abundance in the genome and easy scorable (Kandemir & Kence, 1995;Smith et al, 1997;Bodur et al, 2007;Kekeçoğlu et al, 2009;Özdil et al, 2009;Liu et al, 2016;Rahimi et al, 2016;Haddad et al, 2018;Hassett et al, 2018;Yu et al, 2019;Özdil et al, 2022). Latterly, single nucleotide polymorphisms (SNPs) have been used in population genetics studies, however, thanks to the advantages provided by microsatellites, they could not get ahead of microsatellites even in the genomic era (Zimmerman et al, 2020;Mukherjee et al, 2022;Wang et al, 2022). Genetic diversity and species richness in honey bee populations in Türkiye have been demonstrated by microsatellite and mtDNA studies (Kandemir et al, 2006;Bodur et al, 2007;Ivgin Tunca, 2009;Özdil et al, 2009).…”
Section: Introductionmentioning
confidence: 99%